Restriction modification systems as engines of diversity - Sneppen, Kim; Semsey, Szabolcs; Seshasayee, Aswin S. N.; Krishna, Sandeep (Frontiers in Microbiology, 2015)
Restriction modification (RM) systems provide protection against a broad spectrum of phages. However, the likelihood of a phage permanently bypassing this can be as high as 0.1 per infection (Korona et al., J. Gen. Microbiol. 139: 1283-1290, 1993) which makes for a relatively weak defence. Here we argue that, apart from providing such transient defences, RM systems can facilitate long-term coexistence of many bacterial strains. We show that this diversity can be as large as the burst size of the phage but no larger – a curious correspondence between a number at the level of species and another number at the level of individuals. Such a highly diverse and stably coexisting ecosystem is robust to substantial variation in both bacterial growth rates and strength of their RM systems, which might be one reason why quite weak RM systems exist in the wild.